Three new species and new records of the orb-weaving spider genus Philoponella (Araneae, Uloboridae) from Brazil and Ecuador - Faleiro, Bárbara T.; Santos, Adalberto J. (Zootaxa, 2014)
Three new species of the spider genus Philoponella Mello-Leitão, 1917 are described: Philoponella opelli n. sp. from Brazil and Ecuador, and Philoponella fluviidulcifis n. sp. , and Philoponella duopunctata n. sp. from Brazil. New records for Philoponella vittata (Keyserling, 1881), P. republicana (Simon, 1891), P. fasciata (Mello-Leitão, 1917) and P. divisa Opell, 1979 are provided for Brazil and Ecuador.